2017
DOI: 10.15694/mep.2017.000168
|View full text |Cite
|
Sign up to set email alerts
|

A novel resident-as-teacher curriculum: the role of experiential learning and coaching

Abstract: Background: Canadian family medicine residency programs have the challenge of training in a wide breadth of topics and competencies within a two-year program, including training residents to be effective teachers. There has been a gap in knowledge with regards to the most effective method to train residents to teach. We developed, implemented, and evaluated a novel multi-level resident-as-teacher (RAT) coaching curriculum to provide training and authentic experiences for family medicine residents in teaching m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…[1][2][3][4][5] RAT programs provide opportunities for residents to gain teaching skills through teaching medical students in structured settings, often with support from faculty coaches. 6,7 Several literature reviews of RAT publications have confirmed the benefits of RAT programs for residents, including increased confidence, knowledge of educational principles, and teaching skills. 2,[8][9][10] Yet, the focus of RAT publications has been on a single point in time, usually immediately after completion of the program.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[1][2][3][4][5] RAT programs provide opportunities for residents to gain teaching skills through teaching medical students in structured settings, often with support from faculty coaches. 6,7 Several literature reviews of RAT publications have confirmed the benefits of RAT programs for residents, including increased confidence, knowledge of educational principles, and teaching skills. 2,[8][9][10] Yet, the focus of RAT publications has been on a single point in time, usually immediately after completion of the program.…”
Section: Introductionmentioning
confidence: 97%
“…2,8,9 To address this gap, we examined (a) longitudinal trends in residents' interest, comfort, confidence, skill, and familiarity with clinical teaching during residency and in clinical practice; and (b) teaching involvement in the early years of independent practice after the RAT program. 7…”
Section: Introductionmentioning
confidence: 99%
“…To improve resident teaching skills, Canadian and United States accreditation bodies require that residents be formally trained to teach students (ACGME, 2020;Frank, Snell and Sherbino, 2015). Increasingly, specialties have adapted Resident as Teacher (RaT) initiatives into their residency programs (Al Alchkar et al, 2017); (McKeon et al, 2019;Alaska et al, 2019;Ravichandran et al, 2019) by incorporating a variety of curricula and teaching methodologies (Habermehl, Habermehl and Kim, 2018;Tan et al, 2017;Watkins et al, 2017;Arya et al, 2018;Ricciotti et al, 2017). However, due to increased clinical responsibilities and time constraints, it is a challenge for programs to allocate enough time to enhance their skills (Ravichandran et al, 2019;Habermehl, Habermehl and Kim, 2018;Lacasse and Ratnapalan, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To improve resident teaching skills, Canadian and United States accreditation bodies require that residents be formally trained to teach students ( ACGME, 2020 ; Frank, Snell and Sherbino, 2015 ). Increasingly, specialties have adapted Resident as Teacher (RaT) initiatives into their residency programs ( Al Alchkar et al , 2017 ); ( McKeon et al , 2019 ; Alaska et al , 2019 ; Ravichandran et al , 2019 ) by incorporating a variety of curricula and teaching methodologies ( Habermehl, Habermehl and Kim, 2018 ; Tan et al , 2017 ; Watkins et al , 2017 ; Arya et al , 2018 ; Ricciotti et al , 2017 ). However, due to increased clinical responsibilities and time constraints, it is a challenge for programs to allocate enough time to enhance their skills ( Ravichandran et al , 2019 ; Habermehl, Habermehl and Kim, 2018 ; Lacasse and Ratnapalan, 2009 ).…”
Section: Introductionmentioning
confidence: 99%